2021
DOI: 10.1002/jclp.23225
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder, complex PTSD and subtypes of loneliness among older adults

Abstract: Objectives: Research examining the relationship between loneliness and Complex Posttraumatic Stress Disorder (CPTSD) is scarce, particularly among older adults. CPTSD includes the core symptoms of PTSD along with additional symptoms reflecting "disturbances in self-organisation" (DSO). This study examined the cross-sectional relationships between loneliness (emotional and social loneliness) and CPTSD symptoms (i.e., PTSD and DSO symptoms) in older adults. Methods: Structural equation modelling was used to exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 120 publications
(155 reference statements)
2
21
0
Order By: Relevance
“…We did not observe an interaction effect between age and event type for the anxiety, depression, and substance abuse subdomains. Research conducted prepandemic demonstrated a decline in overall PTSD in older adults, although no difference in the number of PTEs in comparison to other age groups was reported (Fox et al., 2021). The findings on age differences in the association between COVID‐19–related PTEs and mental health have been mixed.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…We did not observe an interaction effect between age and event type for the anxiety, depression, and substance abuse subdomains. Research conducted prepandemic demonstrated a decline in overall PTSD in older adults, although no difference in the number of PTEs in comparison to other age groups was reported (Fox et al., 2021). The findings on age differences in the association between COVID‐19–related PTEs and mental health have been mixed.…”
Section: Discussionmentioning
confidence: 98%
“…The finding that older adults in this sample more often experienced symptoms of insomnia is also consistent with the existing literature showing insomnia rates of around 70% in older adults (Jaussent et al., 2011). This could be associated with the symptoms of hypervigilance and loneliness reported among older adults with PTSD (Fox et al., 2021) but could also be the result of normal changes in sleeping patterns in older age (e.g., an increased number and duration of awakenings and decreased amounts of deep slow‐wave sleep; Van Cauter et al., 2000). In addition, the results show that older adults are more likely to have alcohol‐related symptoms (i.e., substance abuse), which is in line with the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There might be an interaction between these areas such as that a negative self-concept increases the risk of social withdrawal and in turn a lack of positive relational experiences reinforces the negative self-concept . Overall, refugees have a higher risk of loneliness and low social support, factors that have been repeatedly related to higher levels of mental distress [ 62 ], CPTSD [ 63 ] and lower quality of life [ 64 ]. Additionally, we suggest that numbness due to affective dysregulation and an associated reduced self-awareness or ability to engage in interpersonal relationships might further promote disturbances in relationships and a negative self-concept .…”
Section: Discussionmentioning
confidence: 99%
“…Loneliness, defined as the personal perception of unfulfilled intimate, emotional, and social needs (Dykstra, 2009), is known for its detrimental mental and physical health outcomes in the older population (Courtin and Knapp, 2015). Previous studies reported associations between loneliness and PTSD (Shevlin et al, 2015;Itzhaky et al, 2017), with loneliness playing a significant role in contributing to or maintaining CPTSD symptoms (Murphy et al, 2021;Fox et al, 2022). Nevertheless, research regarding the association between loneliness and CPTSD is scarce (Fox et al, 2022), particularly in the older population.…”
Section: Loneliness and Posttraumatic Reactionsmentioning
confidence: 99%